Better‐quality diet is associated with lower odds of severe periodontitis in US Hispanics/Latinos. (11th June 2018) - Salazar, Christian R.; Laniado, Nadia; Mossavar‐Rahmani, Yasmin; Borrell, Luisa N.; Qi, Qibin; Sotres‐Alvarez, Daniela; Morse, Douglas E.; Singer, Richard H.; Kaplan, Robert C.; Badner, Victor; Lamster, Ira B.
Abstract: Aim: We investigated the cross‐sectional association between diet quality and severe periodontitis in a sample of diverse Hispanics from the Hispanic Community Health Study/Study of Latinos. Materials and methods: A total of 13, 920 Hispanic/Latinos aged 18–74 years of different heritages underwent a full‐mouth oral examination and completed two 24‐hr dietary recalls during 2008–2011. Severe periodontitis was defined as having ≥30% tooth sites with clinical attachment loss ≥5 mm. Diet quality was assessed using the Alternative Healthy Eating Index (AHEI‐2010). We evaluated the association of diet quality with severe periodontitis adjusting for age, sex, nativity status, income, education, last dental visit, current insurance, cigarette smoking, diabetes, and energy intake. Results: Relative to those at the lowest quartile of diet quality, individuals at the highest quartile had significantly lower odds of severe periodontitis (adjusted OR = 0.57, 95% CI: 0.39–0.82), with evidence of a dose–response relationship across AHEI quartiles. Among AHEI‐2010 components, higher consumption of whole grains and fruits, and lower consumption of red/processed meats were associated with lower odds of severe periodontitis. Conclusion: Better‐quality diet was associated with lower prevalence of severe periodontitis although the causal pathways need to be clarified in future work.